Prevalence, Characteristics and Antibiogram Profiles of Escherichia coli Isolated from Apparently Healthy Chickens in Mymensingh, Bangladesh (Microbes and Health, 2013)
Escherichia coli known to cause food-borne illnesses worldwide that are closely associated with the consumption of conta-minated poultry and egg products. This study was undertaken for cultural, biochemical and antibiotic sensitivity analyses of E. coli recovered from apparently healthy chickens. Cloacal samples (n=350) were aseptically collected from layers (n=150), broilers (n=150) and indigenous chickens (n=50). The samples were enriched in nutrient broth and streaked onto eosin methylene blue (EMB) agar, MacConkey (MC) agar, blood agar, salmonella-shigella (SS) agar and brilliant green agar (BGA) for cultural characterization of the E. coli isolates. Culture-positive samples yielded characteristic colonies of E. coli with metallic sheen on EMB agar, bright pink or red colonies on MC agar, hemolysis on blood agar, slight pink smooth colonies on SS agar and green color colonies on BGA media. The E. coli isolates produced acid and gas by ferm-enting sugars (dextrose, sucrose, lactose, maltose and mannitol) and gave positive reaction to indole, methyl red (MR) and catalase tests, but were negative to Voges-Proskauer (VP) test. The prevalence of E. coli in layers, broilers and indigenous chickens were 78.67, 82 and 70%, respectively. The antibiotic sensitivity pattern demonstrated that E. coli isolates were mostly sensitive to ciprofloxacin, gentamicin and cephalexin, and resistant to streptomycin, tetracycline, amoxicillin and nalidixic acid. Data of this study suggested that intestine of chicken could be a major reservoir of antibiotic resistant E. coli.DOI: http://dx.doi.org/10.3329/mh.v1i1.13710 Microbes and Health Vol.1(1) June 2012 pp.27-29